2018
DOI: 10.1038/s41598-018-19906-w
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Oxygen Release System to Augment Cell Survival and Promote Cardiac Repair Following Myocardial Infarction

Abstract: Oxygen deficiency after myocardial infarction (MI) leads to massive cardiac cell death. Protection of cardiac cells and promotion of cardiac repair are key therapeutic goals. These goals may be achieved by re-introducing oxygen into the infarcted area. Yet current systemic oxygen delivery approaches cannot efficiently diffuse oxygen into the infarcted area that has extremely low blood flow. In this work, we developed a new oxygen delivery system that can be delivered specifically to the infarcted tissue, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 99 publications
1
79
0
1
Order By: Relevance
“…59 Moreover, in osteoarthritis (OA), the main source of energy metabolism is altered from oxidative phosphorylation to glycolysis, caused by microenvironmental alterations, including hypoxia, evidencing the role of oxygen in chondrocytes metabolism in healthy joints and in the treatment of cartilage degeneration. 59 In accordance with previous studies, 17,21,[60][61][62] these results demonstrated that incorporating oxygen-generating particles within the hydrogel scaffolds could facilitate cell survival for a longer period of time. Thus, the cells may synthesize extracellular matrix, while the scaffolds are gradually being degraded and reabsorbed, ultimately forming new cartilage tissue.…”
Section: Resultssupporting
confidence: 90%
“…59 Moreover, in osteoarthritis (OA), the main source of energy metabolism is altered from oxidative phosphorylation to glycolysis, caused by microenvironmental alterations, including hypoxia, evidencing the role of oxygen in chondrocytes metabolism in healthy joints and in the treatment of cartilage degeneration. 59 In accordance with previous studies, 17,21,[60][61][62] these results demonstrated that incorporating oxygen-generating particles within the hydrogel scaffolds could facilitate cell survival for a longer period of time. Thus, the cells may synthesize extracellular matrix, while the scaffolds are gradually being degraded and reabsorbed, ultimately forming new cartilage tissue.…”
Section: Resultssupporting
confidence: 90%
“…To overcome these issues of PLA different approaches have been adopted such as addition of plasticizers, polymer blending, coupling agents, co-polymerization and nanotechnology [4][5][6]. Many researchers have advocated utilization of nanotechnology due to its multi-folded benefits in addition to mitigation of various short comings of PLA [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Последующее попадание клеток, лишенных межклеточных контактов, в неблагоприятное окружение поврежденной ткани способствует гибели большей части введенных клеток. Поэтому современные экспериментальные протоколы трансплантации клеток, включая ПКС, основаны на введении клеток в составе различных матриксов и гелей [42,43] или в виде тканеинженерных конструкций -клеточных пластов, образованных клетками и наработанным ими внеклеточным матриксом или экзогенным матриксом [10,43]. Это позволяет многократно увеличить выживаемость клеток и повысить эффективность клеточной терапии.…”
Section: стволовые клетки сердца: факт или фантазия?unclassified